THE ROLE OF THE CONTRARIUS ACTUS PRINCIPLE IN OVERSIGHT OF THE GROWTH AND DEVELOPMENT OF COMMUNITY ORGANIZATIONS - Muhammad Yasin Izhharulhaq; Adrian E Rompis; Amelia Cahyadini (Yustisia Jurnal Hukum, 2019)
The term contrarius actus principle is deemed not to exist in Law Number 17 of 2013 on Community Organizations (hereinafter to as CSOs) so that it explicitly states that the Perppu of CSOs contains the principle of contrarius actus in its application. The existence of this principle as referred to in the consideration of the Public Order Perppu lies in the process of applying sanctions where the process is part of the follow-up process of supervisory actions carried out by government officials. Thus, that role in terms of supervision should be studied more deeply in connection with the growth and development of community organizations at this time. The research method with a normative juridical approach, prioritizes library research and its implementation in practice. Research specifications are descriptive. The research phase is carried out through library research, collecting secondary data in the form of primary, secondary, and field research materials to obtain primary data as support. Based on the analysis conducted by the author regarding the role of the principle of contrarius actus in monitoring the growth and development of community organizations, the author raises the role of the principle of contrarius actus in terms of supervision of CSOs as the application of sanctions in the form of administrative sanctions, which are emphasized by the role of responding or reacting to non-compliance with provisions the provisions contained in the decision which in this case are ratification as registered CBOs and also ratification of CSOs as legal entities, in other words that the placement of sanctions in the case of mass organization supervision is a follow-up to the results of monitoring and evaluation by external supervisors with the aim that can control the initial purpose of the establishment of a mass organization that is in accordance with the objectives of the state and national development.